Recent Development of Indonesian Co-Operative Financial Performance: Model that Works in bandung, West Java - Setiaji, Ahmad Yosep; Nugroho, Anggoro Budi (Journal of Business and Management, 2015)
Abstract - Co-operative is an autonomous association of persons; voluntarily united to meet their common economic, social and cultural aspirations and needs through a jointly owned and democratically controlled enterprise (ICA, 2012). International Co-operative Alliances recorded that the problem of Indonesian co-operatives from the Government point of view, the biggest problem that the co-operatives, especially small co-operatives, are facing now is the vulnerability of financial structure (ICA, 2012). This study is aimed to learn about the actual financial condition and performance of co-operatives in Bandung, West Java. The outcome of this research is average financial performance, the distribution of financial condition and the best practice from co-operatives sample in Bandung, West Java. Common tools to observe the financial condition and performance is financial ratio analysis, financial ratio analysis described the financial structure of firm according to the financial aspect and the proportion of each financial data. The method used on this research is Financial Ratio analysis of co-operatives financial data. The financial ratio from co-operatives sample transformed in to financial score using the tools from Indonesia Ministerial decree of Co-operative and Small-Medium enterprises number 06/per/M.KUKM/V/2006 on assessment principle for good performing co-operative scoring. The financial score classified in to several conditions based on score range classification by Indonesia Ministerial decree of Co-operative and Small-Medium enterprises number 22/per/K.UMKM/2007 about co-operative classification performance. The result shows that the average financial performance of co-operative sample in Bandung, West Java have increased continuously in last three years. The distribution of financial condition of co-operatives sample in Bandung, West Java, following the percentage: 62.5% of co-operatives sample are in low financial performance, 37.5% of co-operatives sample are in good financial performance. From 8 co-operatives sample in Bandung, West Java, the best practice from the sample is Primkopau Husein Sastranegara. Primkopau achieved the highest total financial score of all co-operatives sample. From the gap analysis and financial ratio breakdown analysis, the important factor that drives Primkopau performance is:1.Capability to give capital feedback for member.2.Low-debt capital structure.3.High member participation in co-operative financial Capital.